Reconstructing organizational culture in the era of digital transformation: A study of change readiness among employees - Purnawan, Lesna (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
As digital transformation redefines organizational dynamics, understanding how culture influences employees’ readiness for change becomes increasingly critical. This mixed-method study investigates the relationship between organizational culture and change readiness among employees in private universities in Indonesia, a sector under mounting pressure to modernize through digital innovation. Drawing on a quantitative survey (n = 312) and in-depth qualitative interviews (n = 20), the research explores how specific cultural dimensions, psychological dispositions, and leadership perceptions shape change receptivity. The findings reveal that an adhocracy culture significantly enhances readiness for change, with employees responding positively to environments that promote innovation and autonomy. However, a psychological gap emerged wherein motivational commitment to change surpassed beliefs in collective efficacy, indicating a disparity between willingness and perceived capability. Moreover, cultural narratives—embedded in shared experiences and symbols—strongly influence how employees interpret and emotionally respond to organizational change. Leadership behavior was also found to be a decisive factor, as trust in transformational leaders increased acceptance of change. This study contributes theoretically by integrating Schein’s cultural model, Weiner’s theory of organizational readiness, and insights from transformational leadership theory to explain change dynamics in digitally evolving academic institutions. Practically, it offers guidance for human resource and change management strategies in higher education and other knowledge-intensive sectors facing digital disruption.